Is Allergic Rhinitis Associated with Increased Severity Of Coexisting Asthma In Children And Adults? : A Comprehensive Systematic Review - Nydia Ayu Ulima; Dhimas Reyhan Putra; Rajmil Shafira Salsabila (International Medical Journal Corp. Ltd, 2026)
Introduction: Allergic rhinitis (AR) and asthma frequently coexist as manifestations of the unified allergic airway disease, yet the precise relationship between AR and asthma severity remains incompletely characterized across different age groups. This systematic review aimed to synthesize current evidence on whether AR is associated with increased severity of coexisting asthma in children and adults. Methods: A systematic review was conducted following PRISMA guidelines. Studies were screened based on predefined criteria including diagnosed asthma population, AR assessment using validated methods, measurement of asthma severity through clinical parameters, differentiation between allergic and non-allergic rhinitis, and appropriate observational or interventional study designs. Data extraction encompassed study characteristics, population demographics, AR diagnostic criteria, asthma severity measures, association results, age group effects, and effect modifiers. Results: Eighty studies published between 2002-2025 met inclusion criteria, comprising cross-sectional studies (n=62), cohort studies (n=12), systematic reviews (n=2), randomized controlled trials (n=2), and case-control studies (n=2). AR prevalence in asthmatic populations ranged from 29.2% to 97.5% across studies. The majority of studies (72/80, 90%) demonstrated a positive association between AR and increased asthma severity, manifested through poorer asthma control (OR range 1.21-2.74), more frequent exacerbations (incidence rate ratio 1.12), increased healthcare utilization (OR 2.64-2.98 for emergency visits), and impaired lung function (lower FEV₁, FEF₂₅–₇₅). AR severity correlated positively with asthma severity (correlation coefficients 0.365-0.689), with persistent and moderate-to-severe AR phenotypes consistently associated with difficult-to-control asthma. Treatment of AR, particularly with intranasal corticosteroids, was associated with improved asthma outcomes. Age-specific effects included stronger associations in school-age children compared to younger children (<6 years), and attenuation of prevalence in older adults. Discussion: The consistent positive association between AR and asthma severity across diverse populations supports the unified airway concept and has important clinical implications. The dose-response relationship between AR severity and asthma severity, coupled with improved asthma outcomes following AR treatment, suggests potential causal mechanisms including naso-bronchial reflex, systemic eosinophilic inflammation, and shared type-2 inflammatory pathways. However, heterogeneity in AR assessment methods and asthma severity definitions across studies limits direct comparability. Conclusion: Compelling evidence demonstrates that AR is associated with increased severity of coexisting asthma in both children and adults, with AR severity, persistence, and specific phenotypes serving as important determinants. Systematic assessment and optimal management of AR should be integrated into asthma care to potentially improve asthma outcomes.